Prognostic impact of left atrial function in heart failure with preserved ejection fraction in sinus rhythm vs. atrial fibrillation. (14th October 2021) - Schoenbauer, R; Kammerlander, A.A; Duca, F; Aschauer, S; Koschutnik, M; Dona, C; Nitsche, C; Loewe, C; Hengstenberg, C; Mascherbauer, J
Abstract: Background: Left atrial (LA) function is related with outcome in heart failure with preserved ejection fraction (HFpEF). However, how LA function contributes to outcome in the context of atrial fibrillation (AF) versus sinus rhythm (SR) remains unclear. Purpose: To determine the prognostic impact of LA size and phasic function in patients with HFpEF in SR vs. AF. Methods: We enrolled consecutive HFpEF patients and assessed indexed LA volumes (LAVi) and emptying fractions (LA-EF) on cardiac magnetic resonance (CMR) imaging. We prospectively followed patients and used Cox regression models to determine the association of LA size and function with a composite endpoint of heart failure hospitalization and cardiovascular death. Results: A total of 188 patients (71% female, 70±8 y/o) were included of whom 92 (49%) were in persistent AF (Figure 1A). Patients in persistent AF were older (p=0.017) and had a worse NYHA functional class (p=0.003). Compared to SR, peak and minimal LAVi were increased and LA-EF impaired (each p<0.001 respectively) in persistent AF patients (Figure 2A). A total of 65 patients reached the combined endpoint during a follow-up of 31 (9–57) months. Multivariate Cox regression adjusted for established risk factors revealed that LA-EF was significantly associated with outcome in patients in SR (adj.HR 2.14; 95% CI [1.32–3.47] per 1-SD decline, p=0.002). In persistent AF, however, no LA imaging parameter was related to outcome (Figure 1B). By receiver operating characteristic curve and restricted cubic spline- analyses, we identified an LA-EF ≥40% as best indicator for favorable outcomes in patients with HFpEF and SR (Figure 2B). Persistent AF carried a similar risk for adverse outcome compared to impaired LA-EF (<40%) in SR (log-rank, p=0.340) (Figure 1A). Conclusions: In HFpEF patients in SR, impaired LA-EF is independently associated with worse cardiovascular outcome, which is similar to persistent AF. With disease progression including development of persistent AF, LA parameters lose their prognostic ability and thus, are not helpful for further risk stratification. Funding Acknowledgement: Type of funding sources: None.